2018
DOI: 10.1002/ett.3507
|View full text |Cite
|
Sign up to set email alerts
|

Exploring LTE‐V link‐level performance under V‐CPS by geometry enhanced winner II channel model

Abstract: The reliable and efficient simulation of a Long‐Term Evolution‐vehicle requires a channel model that considers practical features of vehicle ad hoc networks, such as large‐scale and small‐scale fading effects from static and mobile objects. However, existing vehicle‐to‐vehicle (V2V) channel models seldom consider vehicle ad hoc networks. In this paper, we propose a geometry‐enhanced WINNER II V2V channel model, which simulates channel responses among vehicles in arbitrary locations with detailed geographical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The WINNER channel model is a popular channel that is used for many applications 26 . The data for this study are obtained using the WINNER channel model and by distributing the UE around each SBS.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WINNER channel model is a popular channel that is used for many applications 26 . The data for this study are obtained using the WINNER channel model and by distributing the UE around each SBS.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The WINNER channel model is a popular channel that is used for many applications. 26 The data for this study are obtained using the WINNER channel model and by distributing the UE around each SBS. In total, 1500 samples were collected, and 80% of data samples were utilized for training, and 20% of data samples were utilized for testing purposes.…”
Section: Dataset Descriptionmentioning
confidence: 99%
“…R ECENT technological advancement in communication has driven many industries toward automation systems, such as cooperative intelligent transport systems [1], droneassisted vehicle communication system [2], smart factory [3], smart farm [4], and smart healthcare [5]. In these systems, many wireless communication links between sensors are constantly used.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the emulator is significantly dependent on the accuracy of the channel models applied. For example, the work in [1] showed that the block error rate curve of a vehicle-to-vehicle wireless system can vary depending on the channel model. As demonstrated in previous studies [11], [12], the statistical properties, including the K-factor, delay spread, path gain, and spatial correlation function, can exhibit significant variations when different channel models are employed in dynamic scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of average consensus, which originated from the field of automata theory and distributed computing [74], has attracted numerous interests for its applications in multiagent/multi-vehicle networks [75], which can efficiently avoid the double counting of data and can facilitate the averaging of the vehicles' initial estimates. This is achieved by sharing their information between vehicles and iteratively update their local estimates.…”
Section: Introductionmentioning
confidence: 99%